TINJAUAN ETIKA BISNIS SYARIAH PADA UD. BANK SAMPAH BINTANG SEJAHTERA - Suastrini, Fatana (Nusantara Hasana Journal, 2021)
This research is entitled Review of Sharia Business Ethics at UD. Bank Sampah Bintang Sejahtera. The method used in this study is a qualitative-descriptive approach because it describes what symptoms exist, which occur in the field in the form of written or spoken words from the practice of buying and selling waste at UD. Bank Sampah Bintang Sejahtera, the source of data in this study is the primary data source obtained from managers, employees, and business partners then secondary data sources such as books, magazines or related internet. With the method of collecting data through observation, interviews, and documentation. The collected data is discussed inductively so that an accurate picture of what actually happened. The results of the analysis in this study indicate that in running its business UD. Bank Sampah Bintang Sejahtera can already be said to follow the existing rules regarding Islamic/Sharia business ethics.